2020
DOI: 10.1080/23802359.2020.1835581
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Korean indigenous stag beetle, Dorcus koreanus

Abstract: In this study, the mitogenome sequences of Korean indigenous stag beetle, Dorcus koreanus , was completely determined by next-generation sequencing analysis. The complete mitogenome of D. koreanus has 15,421 bp in length and consists of 13 protein-coding genes (PCGs), 22 tRNAs, two rRNAs, and one control region. The gene orders and content were identical with previously recorded mitogenomes of Lucanidae species. Phylogenetic analysis based on mitogenome dataset, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ojala et al [ 48 ] reported that the presence of both complete and incomplete stop codons indicates that post-transcriptional RNA processing mechanisms, such as polyadenylation, may be involved in generating the mature mRNA transcripts. RSCU analysis of different studies revealed the four most frequent used codons [ATT (Ile), TTA (Leu), TTT (Phe), and ATA (Met)] in the Dorcus mitogenomes [ 4 , 31 , 32 , 43 ]. These codons exhibit a high usage frequency across the 18 mitogenomes, indicating a preference for specific codons during translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ojala et al [ 48 ] reported that the presence of both complete and incomplete stop codons indicates that post-transcriptional RNA processing mechanisms, such as polyadenylation, may be involved in generating the mature mRNA transcripts. RSCU analysis of different studies revealed the four most frequent used codons [ATT (Ile), TTA (Leu), TTT (Phe), and ATA (Met)] in the Dorcus mitogenomes [ 4 , 31 , 32 , 43 ]. These codons exhibit a high usage frequency across the 18 mitogenomes, indicating a preference for specific codons during translation.…”
Section: Discussionmentioning
confidence: 99%
“…BI allows for the incorporation of prior knowledge and provides an estimation of uncertainty [41], while ML analysis offers a computationally efficient method to infer phylogenetic trees and evaluate alternative evolutionary models, collectively enhancing the accuracy and reliability of phylogenetic reconstructions [42]. Recently, similar methods have been employed for the establishment of phylogenetic relationships among various lucanid taxa, and completely resolved topology characterized by substantial nodal support have been assessed [31,33,43].…”
Section: Introductionmentioning
confidence: 99%